Patatin-related phospholipase pPLAIIIδ increases seed oil content with long-chain fatty acids in Arabidopsis - Li, Maoyin; Bahn, Sung Chul; Fan, Chuchuan; Li, Jia; Phan, Tien; Ortiz, Michael; Roth, Mary R.; Welti, Ruth; Jaworski, Jan; Wang, Xuemin (My University, 2013)
The release of fatty acids from membrane lipids has been implicated in various metabolic and physiological processes, but in many cases, the enzymes involved and their functions in plants remain unclear. Patatin-related phospholipase As (pPLAs) constitute a major family of acyl-hydrolyzing enzymes in plants. Here, we show that pPLAIIIδ promotes the production of triacylglycerols with 20- and 22-carbon fatty acids in Arabidopsis (Arabidopsis thaliana). Of the four pPLAIIIs (α, β, γ, δ), only pPLAIIIδ gene knockout results in a decrease in seed oil content, and pPLAIIIδ is most highly expressed in developing embryos. The overexpression of pPLAIIIδ increases the content of triacylglycerol and 20- and 22-carbon fatty acids in seeds with a corresponding decrease in 18-carbon fatty acids. Several genes in the glycerolipid biosynthetic pathways are up-regulated in pPLAIIIδ-overexpressing siliques. pPLAIIIδ hydrolyzes phosphatidylcholine and also acyl-coenzyme A to release fatty acids. pPLAIIIδ-overexpressing plants have a lower level, whereas pPLAIIIδ knockout plants have a higher level, of acyl-coenzyme A than the wild type. Whereas seed yield decreases in transgenic plants that ubiquitously overexpress pPLAIIIδ, seed-specific overexpression of pPLAIIIδ increases seed oil content without any detrimental effect on overall seed yield. These results indicate that pPLAIIIδ-mediated phospholipid turnover plays a role in fatty acid remodeling and glycerolipid production.
Keywords: Fatty acids; Patatin-related phospholipase As; Acyl-hydrolyzing enzymes; pPLAIIIδ; Arabidopsis thaliana